Concentrated LiODFB Electrolyte for Lithium Metal Batteries - Yu, Juan; Gao, Na; Peng, Jiaxin; Ma, Nani; Liu, Xiaoyan; Shen, Chao; Xie, Keyu; Fang, Zhao (Frontiers in Chemistry, 2019)
Nowadays, lithium (Li) metal batteries arouse widespread concerns due to its ultrahigh specific capacity (3860 mAh g-1). However, the growth of Li dendrites has always limited their industrial development. In this paper, the use of concentrated electrolyte with lithium difluoro(oxalate)borate (LiODFB) salt in 1, 2-dimethoxyethane (DME) enables the good cycling of a Li metal anode at high Coulombic efficiency (up to 98.1%) without dendrite growth. Furthermore, a Li/Li cell can be cycled at 1 mA cm-2 for over 3000 hours. Besides, compared to conventional LiPF6-carbonate electrolyte, Li/LiFePO4 cells with 4 M LiODFB-DME exhibit superior electrochemical performances, especially at high temperature (65 °C). These outstanding performances can be certified to the increased availability of Li+ concentration and the merits of LiODFB salt. We believe that the concentrated LiODFB electrolyte is help to enable practical applications for Li metal anode in rechargeable batteries.